# What is the answer for question 4.b)? (Draw 2) http://postimg.org/image/q8ectggh3/

*print*Print*list*Cite

### 1 Answer

You need to notice that the given graph is a parabola whose vertex (h,k) = (3,-7), hence, you may write the vertex form of quadratic corresponding function, such that:

`f(x) = a(x - h)^2 + k`

Considering a = 1 and replacing 3 for h and -7 for k yields:

`f(x) = (x - 3)^2 - 7`

You need to sketch the graph of the transformed function `y = -4f(x) - 2,` hence, you need to take it step by step, such that:

- performing the multiplication `-4*f(x)` yields:

`-4*f(x) = -4((x - 3)^2 - 7) => y = -4(x - 3)^2 + 28`

Since a = -4, you need to flip the graph, hence, parabola opens downward now, such that:

- you need to shift down by 2 units, `y =-4(x - 3)^2 + 28 - 2 => y =-4(x - 3)^2 + 26` , hence the new graph is represented by the red parabola, such that: